Electromagnetically Induced Transparency Spectra of 6Li Rydberg Atoms - Meimei Wu; Xin Bao; Shuxian Yu; Licheng Yi; Pingshuai Ren; Shujin Deng; Haibin Wu (Photonics, 2023)
Rydberg atoms possess highly excited valence electrons that are far away from atomic cations. Compared with ground states, Rydberg states are excited states with a high principal quantum number n that exhibit large electric dipole moments and have a variety of applications in quantum information processing. In this communication, we report the measurement of the <semantics>6</semantics>Li Rydberg excitation spectrum by ladder-type electromagnetically induced transparency (EIT) in a vapor cell. The 2<semantics>p→ns/nd</semantics> EIT spectra were recorded by sweeping the frequency of an ultraviolet Rydberg pumping laser while keeping the probing laser resonant to the <semantics>2s→2p</semantics> transition. All lasers were locked on an ultrastable optical Fabry-Pérot cavity and measured by an optical frequency comb. Our results provide valuable information to precisely determine quantum defects and enable novel experiments with Rydberg-dressed ultracold Fermi gases.